(untitled) (Vietnam Journal of Community Medicine, 2022)
Objectives: The study was carried out with the aim of comparing the analgesic effect of local anesthesia with general anesthesia in cesarean section at Nghe An Obstetrics and Children’s Hospital. Methods: Research 120 patients undergoing cesarean section with ASA I and II, aged 18 to 42 years, who were divided into two groups: group A (n=60) decreased Post-operative pain with anaropine combined with fentanyl via local anesthetic and group B (n=60) postoperative analgesia with intravenous paracetamol and intramuscular morphine. Evaluation of results by monitoring VAS pain scale, unwanted effects and complications in 24 hours after surgery. Results: Results did not differ between the two groups in terms of age, weight, ASA, and time of surgery. The average VAS pain score in group A was lower than in group B at all time points of follow-up (p<0.05). In the first 24 hours after surgery, the rate of patient satisfaction in group A is 100%, of which 73.33% are very satisfied; group B, the rate of satisfied patients is 95%, of which 45% are very satisfied. Group A had 2 patients (3.33%) and MP group had 12 patients (20%) with nausea and vomiting (p <0.05). Conclusions: Epidural anesthesia with anaropine 0.1% plus fentanyl 1mcg/ml has analgesia quality and maternal satisfaction (100% of women are satisfied, of which 73.33% are very satisfied) better than analgesia with static paracetamol intramuscular morphine combination (95% of women are satisfied, of which 45% are very satisfied) in cesarean section. Epidural anesthesia with anaropine 0.1% plus fentanyl 1 mcg/ml is a safe technique, with fewer side effects and undesirable effects (1.67% of women with itching and 3.33% of nausea and vomiting) than using intravenous paracetamol combined with intramuscular morphine (20% of women have vomiting, nausea).